1988
DOI: 10.1002/bod.2510090607
|View full text |Cite
|
Sign up to set email alerts
|

Drug distribution in dog brain studied by positron emission tomography

Abstract: We used positron emission tomography to monitor the distribution of radioactivity in dog brain and muscle following i.v. administration of 11C-labelled antipyrine, imipramine, and quinidine. Twenty-five sequential scans of a transaxial slice of the head were performed within 90 min; radioactivity in plasma was measured in a gamma-counter. Following i.v. injection of [11C]antipyrine (50 mg kg-1; 9-68 mCi; n = 10), the decay of plasma activity was accompanied by rapid uptake in brain and variable uptake in muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…2). This is in line with the observations previously made in the dog (Hiatt et al 1945;Agon et al 1988)• However, quinidine does penetrate the barrier and is found at a low concentration (10-15 nmol. 1-1) in the cerebrospinal fluid.…”
Section: Quinidine Penetration Of the Blood Brain Barriersupporting
confidence: 92%
See 2 more Smart Citations
“…2). This is in line with the observations previously made in the dog (Hiatt et al 1945;Agon et al 1988)• However, quinidine does penetrate the barrier and is found at a low concentration (10-15 nmol. 1-1) in the cerebrospinal fluid.…”
Section: Quinidine Penetration Of the Blood Brain Barriersupporting
confidence: 92%
“…Hiatt and Quinn found that cerebrospinal fluid/plasma and brain tissue/plasma concentration ratios of quinidine were 50-100 times lower than liver tissue/plasma ratio in dogs after a 2 h intravenous infusion of quinidine. The positron emission tomography study by Agon et al (1988) was also performed in dogs and showed a similar relationship between the plasma and brain levels of quinidine. Codeine is O-demethylated to morphine in brain tissue from rats (Chen et al 1990).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation